Identifying obstacles hindering the conduct of academic-sponsored trials for drug repurposing on rare-diseases: an analysis of six use cases - Del Álamo, Marta; Bührer, Christoph; Fisher, Dirk; Griese, Matthias; Lingor, Paul; Palladini, Giovanni; Sireau, Nicolas; Hivert, Virginie; Sangiorgi, Luca; Guillot, Florence; Halftermeyer, Juliane; Soucková, Lenka; et al. (Trials, 2022)
BACKGROUND: Academic-sponsored trials for rare diseases face many challenges; the present paper identifies hurdles in the set-up of six multinational clinical trials for drug repurposing, as use cases. METHODS: Six academic-sponsored multinational trials aiming to generate knowledge on rare diseases drug repurposing were used as examples to identify problems in their set-up. Coordinating investigators leading these trials provided feedback on hurdles linked to study, country, and site set up, on the basis of pre-identified categories established through the analysis of previous peer-reviewed publications. RESULTS: Administrative burden and lack of harmonization for trial-site agreements were deemed as a major hurdle. Other main identified obstacles included the following: (1) complexity and restriction on the use of public funding, especially in a multinational set up, (2) drug supply, including procurement tendering rules and country-specific requirements for drug stability, and (3) lack of harmonization on regulatory requirements to get trial approvals. CONCLUSION: A better knowledge of the non-commercial clinical research landscape and its challenges and requirements is needed to make drugs-especially those with less commercial gain-accessible to rare diseases patients. Better information about existing resources like research infrastructures, clinical research programs, and counseling mechanisms is needed to support and guide clinicians through the many challenges associated to the set-up of academic-sponsored multinational trials.
Keywords: klinické zkoušky jako téma; Rare Diseases; Randomized clinical trials; Clinical Trials as Topic; vzácné nemoci; organizace; Drug repurposing; Challenges; Drug Repositioning; Barriers; Humans; Organizations; přehodnocení terapeutických indikací léčivého přípravku; Rare diseases; Academic-sponsored; lidé